Evaluation of Microstructure, and Mechanical Properties of Superalloy 59 and 904L Dissimilar welds using Hot Wire Turbo TIG - N. Muthukumaran; B. Arulmurugan; R. Sureshkumar; R. Bharathikanna (Archives of Metallurgy and Materials, 2025)
This research involves the dissimilar welding of a novel combination of superalloy 59 and 904L using Hot Wire Turbo TIG welding (HWTT) with ERNiCrMo-13 filler wire. Macroscopic examination revealed defect-free welds with optimized geometry and minimal heat-affected zone. The bead geometry, influenced by capillary action and the Marangoni effect, exhibited a 7 mm crest width, 5.5 mm center width, and 2.6 mm depth. Microstructural analysis through FESEM and EDS revealed a substantial 32.06% Mo-enriched secondary phase in the fusion zone, vital for structural reliability and enhancing weldment mechanical properties. Hardness testing revealed 15% higher values in the weld joint compared to base metals. Cryogenic treatment enhanced the weldment tensile strength by up to 10%, with deep cryogenic treatment (DCT) surpassing as-welded samples by 9.5%. Tensile and impact tests, along with fractography images, revealed microstructure-influenced ductile fractures. Charpy impact toughness of the weld fusion zone, at 89 J, showcases favorable properties, 2% lower than alloy 59 but 11.2% higher than 904L, attributed to DCT.